Open access to mobile assisted language learning supported by the Mobile2Learn framework - Sampson, Demetrios; Zervas, P. (2012)
Over the past years, a wide range of Technology-enhanced Learning (TeL) systems have been developed, which have significantly influenced the field of foreign languages teaching and learning. This is widely known as Technology-enhanced Language Learning (TELL). On the other hand, the widespread ownership of mobile devices and the potential benefits that they can provide to the learning process has attracted the attention of both researchers and practitioners in the field of TELL. This has led to the development of a new approach for TELL, which is commonly referred to as Mobile Assisted Language Learning (MALL). Nevertheless, although during the last years a number of MALL systems have been developed, most of them do not concern with open access to language learning resources and practices. As a result, neither re-use of language learning resources not sharing of best technology-facilitated language teaching practices among the communities of educational practitioners and educational organizations is directly facilitated. In this paper, we propose the Mobile2Learn Framework, which aims at providing tools and services that facilitate open access to mobile-assisted language digital learning resources and courses, and we present a case study from its implementation. © 2012 IEEE.